Monkeypox Skin-Lesion Detection with a Modified VGG16 and a Lightweight Custom CNN. - Lavanya, Komati; Rudrarapu, Rajakumar; Vandana, Palle; Nowsheen, Gazala (Journal of Neonatal Surgery, 2025)
Rapid, accurate recognition of monkeypox skin lesions from clinical photographs can support triage when laboratory testing is delayed or unavailable. We propose a hybrid deep-learning pipeline that couples a modified VGG16 backbone (initialized with ImageNet weights and fine-tuned on lesion images) with a custom lightweight CNN head for domain-specific feature refinement. The workflow (Fig. 1) comprises dataset curation, stratified train/test splitting, color/illumination normalization, lesion-aware augmentations (random crop, flip, scale, blur, JPEG artifacts), and class-imbalance handling via focal loss and mixup. The modified VGG16 replaces fully connected layers with global average pooling and dropout, integrates depthwise-separable bottlenecks to reduce parameters, and uses label-smoothing at the softmax output. A compact custom CNN branch in parallel learns texture-scale patterns typical of vesicular/pustular lesions; both streams are fused by attention-based feature concatenation before the final classifier. Evaluation uses accuracy, precision, recall, F1, ROC–AUC, Cohen’s κ, and calibration (ECE), with patient-level grouping to avoid leak. Grad-CAM visualizations provide clinical interpretability by highlighting lesion regions influencing predictions. The approach is designed for deployment on modest hardware and tele-dermatology workflows. Results demonstrate that combining transfer learning with a purpose-built CNN head yields substantial gains over single-backbone baselines, improving sensitivity to early, small, or low-contrast lesions while maintaining strong specificity against confounders (acne, varicella, molluscum)..